(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This article is part of the assessment of the impact of crime and corruption on the management strategies of micro and small enterprises in the municipality of Teapa, Tabasco, the information was collected through a quantitative instrument with a five-point Likert scale for systemic analysis and with dichotomous questions, a cross-cutting and descriptive investigation was carried out, with a sample of 465 mypes5 mypes, the effect of crime and corruption on the decision-making of the directors of the mypes of the municipality cited was valued. The scores of each systemic analysis variable were compared in companies that have been victimized and have not been victimized. In addition, the effect of the perception of these variables and how it affects businesses were analyzed by linear regressions.